2013
DOI: 10.7554/elife.00133
|View full text |Cite
|
Sign up to set email alerts
|

Kinesin-1 regulates dendrite microtubule polarity in Caenorhabditis elegans

Abstract: In neurons, microtubules (MTs) span the length of both axons and dendrites, and the molecular motors use these intracellular ‘highways' to transport diverse cargo to the appropriate subcellular locations. Whereas axonal MTs are organized such that the plus-end is oriented out from the cell body, dendrites exhibit a mixed MTs polarity containing both minus-end-out and plus-end-out MTs. The molecular mechanisms underlying this differential organization, as well as its functional significance, are unknown. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
156
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(170 citation statements)
references
References 53 publications
14
156
0
Order By: Relevance
“…Importantly, the ability of KHC mutA to bind many cargo adapters and transport cargoes was similar to wild-type KHC. This finding is in agreement with a study in Caenorhabditis elegans, which demonstrated that a similar mutation in the C-terminal MT-binding site of kinesin-1 did not affect mitochondria transport (11).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Importantly, the ability of KHC mutA to bind many cargo adapters and transport cargoes was similar to wild-type KHC. This finding is in agreement with a study in Caenorhabditis elegans, which demonstrated that a similar mutation in the C-terminal MT-binding site of kinesin-1 did not affect mitochondria transport (11).…”
Section: Discussionsupporting
confidence: 82%
“…Khc mutA larvae display reduced dendritic branching and total dendrite length in class I and IV da neurons, suggesting that MT sliding is important for arborization. This result is consistent with a previous study in C. elegans, where the authors demonstrate that mutations in the C terminus of the kinesin-1 ortholog, unc-116, result in dendritic phenotypes in vivo (11). A unc-116 truncation mutant lacking the C terminus, including the MT-binding site, displayed axon-like MT polarity in dendrites, as well as mislocalization of axonal cargoes to dendrites.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Motor proteins either anchored to the cell cortex or spanning two microtubules can facilitate the sliding of preassembled microtubules from the soma into the dendrite. 6,25 In addition, as the dendrite arbor elaborates and after it reaches the mature state, microtubule motor proteins maintain and enhance the minus-end distal population by selectively removing plus-end distal microtubules 30 and guiding new polymerization events passing through dendrite branch points in the retrograde direction. 31 A second mechanism is via the nucleation of microtubules, i.e., de novo initiation of microtubule polymerization within a nascent dendrite branch.…”
mentioning
confidence: 99%
“…It has been suggested that the minus-end out MT organization in neurons is maintained by steering of polymerizing MTs along the stable MTs by kinesin-2 motors bound to growing MT plus ends Doodhi et al 2014). Other motor proteins, such as kinesin-1, might also be able to crosslink antiparalleled MTs and are critical in forming the characteristic minus-end out MT organization of C. elegans dendrites (Yan et al 2013).…”
Section: Organization Of Axonal and Dendritic Microtubulesmentioning
confidence: 99%